2021
DOI: 10.3389/fnbeh.2021.766745
|View full text |Cite
|
Sign up to set email alerts
|

A Preclinical Model of Computerized Cognitive Training: Touchscreen Cognitive Testing Enhances Cognition and Hippocampal Cellular Plasticity in Wildtype and Alzheimer’s Disease Mice

Abstract: With the growing popularity of touchscreen cognitive testing in rodents, it is imperative to understand the fundamental effects exposure to this paradigm can have on the animals involved. In this study, we set out to assess hippocampal-dependant learning in the APP/PS1 mouse model of Alzheimer’s disease (AD) on two highly translatable touchscreen tasks – the Paired Associate Learning (PAL) task and the Trial Unique Non-Matching to Location (TUNL) task. Both of these tests are based on human tasks from the Camb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…This trend is likely a flooring effect, as performance levels on 0-s delay trials decreased by 5–15% when delay trials were added, particularly in the two older cohorts, and continued to decline with increased delays, reaching accuracy levels of approximately 50%. Similarly, performance in 6-s delay trials has been noted in past studies, with some mice performing at chance level ( Kim et al, 2015 ; Shepherd et al, 2021 ). To mitigate such flooring effects, future studies may consider reducing difficulty by including only one delay and testing it at a single separation level per session.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This trend is likely a flooring effect, as performance levels on 0-s delay trials decreased by 5–15% when delay trials were added, particularly in the two older cohorts, and continued to decline with increased delays, reaching accuracy levels of approximately 50%. Similarly, performance in 6-s delay trials has been noted in past studies, with some mice performing at chance level ( Kim et al, 2015 ; Shepherd et al, 2021 ). To mitigate such flooring effects, future studies may consider reducing difficulty by including only one delay and testing it at a single separation level per session.…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, although the TUNL and 5-CSRTT tasks did not directly target behavioral flexibility, the transition between these tasks could have inadvertently trained this ability. Noteworthy is the previous finding that experience with the TUNL task improved performance in the Morris Water Maze ( Shepherd et al, 2021 ), indicating that touchscreen training can impact tasks in the same cognitive domain, like spatial working memory, even in drastically different testing environments. In that study, mice with TUNL experience also showed increased hippocampal neurogenesis, linked to enhanced reversal learning abilities ( Anacker and Hen, 2017 ).…”
Section: Discussionmentioning
confidence: 98%